Intervencijski posegi v dojki - Vargazon, Tomaž (Radiology and oncology (Ljubljana), 1998)
This article is a revision about interventions in breast, it describes the procedure, indications and contraindications in different breasts interventions made on Oncological Institut in Ljubljana. According to the regulations the interventions are made only by radiologist-mammologist is the central and key person of mammological team, composed by the experienced clinics, pathologist, cytologist and surgeon.
Keywords: Biopsy; bolezni; Breast diseases; diagnostika; dojke; mamografija; novotvorbe; Pathology; radiografija; Radiography, interventional